IMPACT OF ARMED CONFLICT ON TOURISM IN KASHMIR - PEER AMIR AHMAD (RADJA PUBLIKA, 2022)
Many countries around the world rely heavily on tourism to support their economies. According to legend, Kashmir is known around the world as